1995
DOI: 10.1128/jb.177.13.3885-3889.1995
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that operons tcb, tfd, and clc encode maleylacetate reductase, the fourth enzyme of the modified ortho pathway

Abstract: The maleylacetate reductase from Pseudomonas sp. strain B13 functioning in the modified ortho pathway was purified and digested with trypsin. The polypeptides separated by high-performance liquid chromatography were sequenced. Alignments with the polypeptides predicted from the tfdF and tcbF genes located on plasmids pJP4 of the 2,4-dichlorophenoxyacetate-degrading Alcaligenes eutrophus JMP134 and pP51 of the 1,2,4-trichlorobenzene-degrading Pseudomonas sp. strain P51 as well as polypeptides predicted from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 27 publications
1
27
1
Order By: Relevance
“…However, a low level of dienelactone (4-carboxymethylenebut-2-ene-4-olide) hydrolase activity and an even lower activity against 2-chloromuconate were observed in strains containing module II genes, whereas a very poor maleylacetate reductase activity was found in strains containing only module I (34). Therefore, despite its high similarity to genes encoding functional maleylacetate reductases (19), tfdF I has been said to encode a poor or nonfunctional enzyme. Moreover, attempts to purify maleylacetate reductase from R. eutropha JMP134 yielded a protein with an N-terminal sequence matching that of TfdF II (45), indicating a critical role of TfdF II for growth of strain JMP134 on 2,4-D.…”
mentioning
confidence: 90%
“…However, a low level of dienelactone (4-carboxymethylenebut-2-ene-4-olide) hydrolase activity and an even lower activity against 2-chloromuconate were observed in strains containing module II genes, whereas a very poor maleylacetate reductase activity was found in strains containing only module I (34). Therefore, despite its high similarity to genes encoding functional maleylacetate reductases (19), tfdF I has been said to encode a poor or nonfunctional enzyme. Moreover, attempts to purify maleylacetate reductase from R. eutropha JMP134 yielded a protein with an N-terminal sequence matching that of TfdF II (45), indicating a critical role of TfdF II for growth of strain JMP134 on 2,4-D.…”
mentioning
confidence: 90%
“…Although the maleylacetate reductase gene, tfdF, of Ralstonia eutropha JMP134(pJP4) was initially misinterpreted as encoding a chlorodienelactone isomerase (Don et al, 1985), the chlorocatechol gene clusters of pJP4, pAC27, Pseudomonas sp. B13, and pP51 by DNA sequencing, by correspondence of experimentally determined N-terminal sequences to sequences predicted from DNA and by expression of cloned genes, were shown to contain maleylacetate reductase genes in addition to genes for chlorocatechol 1,2-dioxygenases, chloromuconate cycloisomerases and dienelactone hydrolases (Frantz & Chakrabarty, 1987;Perkins et al, 1990;Laemmli et al, 2000;van der Meer et al, 1991;Schell et al, 1994;Kasberg et al, 1995Kasberg et al, , 1997Seibert et al, 1993;Plumeier et al, 2002). Sequence similarities suggest that this is true also for the chlorocatechol gene clusters of various other plasmids or strains.…”
Section: Introductionmentioning
confidence: 99%
“…B13, and pP51 by DNA sequencing, by correspondence of experimentally determined N-terminal sequences to sequences predicted from DNA and by expression of cloned genes, were shown to contain maleylacetate reductase genes in addition to genes for chlorocatechol 1,2-dioxygenases, chloromuconate cycloisomerases and dienelactone hydrolases (Frantz & Chakrabarty, 1987;Perkins et al, 1990;Laemmli et al, 2000;van der Meer et al, 1991;Schell et al, 1994;Kasberg et al, 1995Kasberg et al, , 1997Seibert et al, 1993;Plumeier et al, 2002 During growth with 4-fluorobenzoate, R. eutropha 335 T and R. eutropha JMP222, a pJP4-free derivative of the 2,4-dichlorophenoxyacetate-utilizing strain JMP134, induce a maleylacetate reductase, but not the other enzymes typical for chlorocatechol catabolism (Schlömann et al, 1990a). Thus, these strains contain a presumably chromosomal maleylacetate reductase gene of still unknown metabolic affiliation.…”
Section: Introductionmentioning
confidence: 99%
“…While the genes tcbCDE, tfdCDE, and clcABD have long been known to encode chlorocatechol 1,2-dioxygenase, chloromuconate cycloisomerase, and (chloro)dienelactone hydrolase, respectively, information on the functions of the TcbF, TfdF, and ClcE gene products were obtained more recently. After it had been reported that TcbF and TfdF are homologous to ironcontaining alcohol dehydrogenases (19), our groups provided evidence that these proteins and ClcE encoded by pAC27 are in fact maleylacetate reductases (9,16,18). This paper deals with the isolation of the maleylacetate reductase gene from Pseudomonas sp.…”
mentioning
confidence: 99%